Use of a Bioprosthetic Mesh in Complex Hernia Repair: Early Results From a French Multicenter Pilot Study. (December 2014) - Lupinacci, Renato Micelli; Gizard, Anne Sophie; Rivkine, Emmanuel; Debove, Clotilde; Menegaux, Fabrice; Barrat, Christophe; Wind, Philippe; Trésallet, Christophe
Background. Implantation of synthetic meshes for reinforcement of abdominal wall hernias can be complicated by mesh infection, which often requires mesh explantation. The risk of mesh infection is increased in a contaminated environment or in patients who have comorbidities such as diabetes or smoking. The use of biological prostheses has been advocated because of their ability to resist infection. Initial results, however, have shown high hernia recurrence rates and wound occurrences. The objective of the present study is to evaluate early and mid-term outcomes in the largest French series that included 43 consecutive complex abdominal hernias repaired with biological prostheses. Materials and methods. Retrospective observational study of a prospective collected data bank. Patient demographics, history of previous repairs, intraoperative findings and degree of contamination, associated procedures, postoperative prosthetic-related complications, and long-term results were retrospectively reviewed. Results. There were 25 (58%) incisional, 14 parastomal, and 4 midline hernia repairs. Hernias were considered "clean" (n = 5), "clean-contaminated" (n = 19), "contaminated" (n = 12), or "dirty" (n = 7). Wound-related morbidity occurred in 17 patients; 4 patients needed reoperation for cutaneous necrosis or abscess. Smoking was the only risk factor associated with wound complication ( P = .022). No postoperative wound events required removal of the prosthesis. There were 4 hernia recurrences (9%). A previous attempt at repair ( P = .018) and no complete fascia closure ( P = .033) were associated with hernia recurrence. Conclusions. This study demonstrated that the use of bioprothesis in complex hernia repair allowed successful single-stage reconstruction. Wound-related complications were frequent. Cost-benefit analyses are important to establish the validity of these findings.